The gnats of Knotty Pine - Peet, Bill. (Boston : Houghton Mifflin, 1975)
The smallest creatures of Knotty Pine Forest avert the horrors of the hunting season in a very "sportsgnatlike" way.
Keywords: Hunting stories; Animals -- Fiction